Inequality in the Access to Secondary Education and Rural Poverty in Bangladesh: An Analysis of Household and School Level Data - Alia Ahmad; Mahabub Hossain; Manik Lal Bose (Lund University, School of Economics and Management, Department of Economics, 2005)
This paper explores the relationship between different levels of education and poverty through an analysis of household-level data from 60 villages in Bangladesh. First of all, it depicts the overall trend in school enrollment at primary and secondary level between 1988-2000, and confirms the inequality that exists in the access to education at post-primary level. This is followed by a presentation of income and occupation data that show a strong positive correlation with the level of education. In the second part, an income function analysis has been done to assess the impact of education along with other determinants. Marginal returns to upper secondary and primary level of education have been found to be higher than lower secondary education. The third part analyzes the effects of education on child/woman ratio, and on the secondary school participation rate of male and female children. Both poverty and low education have positive but weak effect on child/woman ratio. On the other hand, school participation rates are strongly affected by the income status of the household and education of father and mother. Mothers education has stronger effect on girls enrollment in seconadry schools. Lastly, the analysis of school-level data confirms the findings from household survey such as the absence of gender gap at primary level and higher proportion of girls in some secondary schools. The unexpectedly high promotion rates in secondary schools suggest that the schools are more concerned about government financial support than the quality of education. High degree of private tuition among secondary school teachers also points toward inequality in the access to quality education that impairs the ability of the poor to complete the secondary level.
Keywords: I20; I21; 330; poverty; returns to secondary education; inequality